TAXATION AND WELFARE: MEASURING THE EFFECT OF BULGARIA’S 2007-08 CORPORATE-PERSONAL INCOME TAX REFORMS - VASILEV, Aleksandar (Theoretical and Practical Research in Economic Fields; Vol 10 No 2 (2019): TPREF, Volume X, Issue 2(20), Winter 2019, 2019)
This paper utilizes a simple general-equilibrium model to analyse the long-run effects of Bulgaria’s 2007-08 corporate-personal income tax reforms. In particular, we consider the effect working through the firm’s capital structure and argue that the new reforms incentivize firms to increase investment, as the new regime benefits retained earnings. The increase in capital increases output and productivity, which in turn increases consumption and welfare. On average, households are enjoying 8.65% higher consumption in the new steady-state in the benchmark scenario. As a robustness check, we allow for a variable labour supply, where the gain increases further by additional 3.9% of consumption, to produce an overall gain of 13.55%.